Perancangan Produk Kerajinan untuk Home Industry Berbasis E- Commerce dengan Integrasi OpenChart sebagai Media Promosi Digital - An Naufal, Hafizh; Annas, Firdaus; Yupada Putri Sitorus, Nazwa; Janahtan, Khalif (JOVISHE : Journal of Visionary Sharia Economy, 2024)
This article discusses the importance of designing craft products in the context of home industry and e-commerce, as well as practical steps for developing products that can be sold online. Although many micro, small and medium enterprise (MSME) owners have not utilized online media for promotion, this research shows that implementing the OpenCart platform can increase product visibility. Current conditions show that MSME owners often lack confidence in marketing products online, which results in limited market reach. Using the Research and Development (R&D) methodology through the Define, Design, Develop and Dissemination model, this research produces web-based promotional media using the OpenCart application. The findings show that OpenCart functions as an effective supporting tool to increase the competitiveness of home industry products in the region. The implications of this research are the ability of MSMEs to be known outside the region, increase competitiveness in product promotion, and strengthen human resources to be able to compete globally. Thus, it is hoped that this article can inspire entrepreneurs to take advantage of opportunities in the e-commerce market. Technological developments have brought changes to product marketing and sales, especially for Micro, Small and Medium Enterprises (MSMEs). This research aims to develop an E-Commerce based sales strategy for MSMEs in the craft sectors in Padang City, as an effort to increase competitiveness and expand market access.